Terapia ocupacional na área da gerontologia: uma revisão de escopo - Camponogara, Bruna Tainá Bordin (2024)
The objective of this work was to identify the trends of the most recent studies of Occupational Therapy in Gerontology based on two Brazilian journals in the area (Cadernos Brasileiros em Terapia Ocupacional and the Revista de Terapia Ocupacional da USP), as well as the most used in research (Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), National Library of Medicine (Pubmed). The methodology used was the scooping review of articles published between 2013 and 2023. The selected articles were analyzed, and the following themes are presented: Performance of Occupational Therapy in Gerontology; Effects of Occupational Therapy Interventions on Aging; Assessment Instruments and Occupational Therapy Protocols focused on Gerontology; and Others. It was concluded that the majority of Occupational Therapy publications in Gerontology in the last 10 years were carried out in Brazil, were based on quantitative methodological approaches, highlighting the use of randomized clinical trials, but in Brazilian publications, there is still a predominance of qualitative approaches, and the majority of selected studies are analyzes of the effects of Occupational Therapy interventions on aging. Although the Federal Council of Physiotherapy and Occupational Therapy recognized gerontology as a professional specialty of occupational therapy in 2016, there was no increase in the number of publications involving the topic in recent years.